Pupil Diameter Changes in High Myopes after Collamer Lens Implantation. Issue 12 (December 2015) - Li, Dan; Yang, Yabo; Su, Caipei; Yin, Houfa; Liu, Xue
ABSTRACT: Purpose: To observe the changes in pupil size under photopic and scotopic conditions after Implantable Collamer Lens (ICL) implantations in eyes with high myopia. Methods: The ICL was implanted in 90 eyes belonging to 45 patients with high myopia. Photopic pupil diameters, scotopic pupil diameters, anterior chamber depths, and ICL vaults were examined at the preoperative, postoperative 1-month, and postoperative 3-month stages. The preoperative and postoperative photopic pupil diameters and scotopic pupil diameters were also compared with each other to note the differences between them. The correlations between preoperative and postoperative pupil diameter changes under different light conditions and presurgical refractive error were analyzed alongside patient's age and ICL vault. Results: Pupil diameters at both postoperative 1-month and postoperative 3-month stages were smaller than those before operation in distinct light environments, as well as pupil constriction amplitude. Correlation analysis showed that there was a statistically significant correlation between pupil diameter changes under different light conditions and presurgical refractive error at 1 month and 3 months after ICL implantation; pupil diameter decreased more when presurgical refractive error powers were less myopic. Statistically significant correlations were not found, however, with patient's age and ICL vault. Postoperative 1-month and mean postoperative 3-month anterior chamber depths were decreased when compared with preoperative anterior chamber depths. Statistically significant correlations were found in change in preoperative and postoperative anterior chamber depth and ICL vault. No statistically significant difference was found between ICL vault at the postoperative 1-month and postoperative 3-month stages. Conclusions: Pupil diameter may decrease at the 1- and 3-month stages after ICL implantation under both photopic and scotopic conditions. This indicates that reduction of pupil diameter may be caused by mechanical contact between the ICL and the posterior iris surface.